Effects of substrate stress and light intensity on enhanced biological phosphorus removal in a photo-activated sludge system. (1st February 2021) - Mohamed, A.Y.A.; Welles, L.; Siggins, A.; Healy, M.G.; Brdjanovic, D.; Rada-Ariza, A.M.; Lopez-Vazquez, C.M.
Highlights: Effective P removal has been achieved using a model-based design approach Nitrogen limitation can influence P removal negatively in an EBPR-PAS system Controlling NH4 and HCO3 is critical to balancing PAOs and microalgae populations The performance of the EBPR-PAS system was robust at different light intensities Abstract: Photo-activated sludge (PAS) systems are an emerging wastewater treatment technology where microalgae provide oxygen to bacteria without the need for external aeration. There is limited knowledge on the optimal conditions for enhanced biological phosphorus removal (EBPR) in systems containing a mixture of polyphosphate accumulating organisms (PAOs) and microalgae. This research aimed to study the effects of substrate composition and light intensity on the performance of a laboratory-scale EBPR-PAS system. Initially, a model-based design was developed to study the effect of organic carbon (COD), inorganic carbon (HCO3 ) and ammonium-nitrogen (NH4 -N) in nitrification deprived conditions on phosphorus (P) removal. Based on the mathematical model, two different synthetic wastewater compositions (COD:HCO3 :NH4 -N: 10:20:1 and 10:10:4) were examined at a light intensity of 350 µmol m −2 sec −1 . Add to this, the performance of the system was also investigated at light intensities: 87.5, 175, and 262.5 µmol m −2 sec −1 for short terms. Results showed that wastewater having a high level of HCO3 and low level of NH4 -N (ratio of 10:20:1) favored only microalgal growth, and had poor P removal due to a shortage of NH4 -N for PAOs growth. However, lowering the HCO3 level and increasing the NH4 -N level (ratio of 10:10:4) balanced PAOs and microalgae symbiosis, and had a positive influence on P removal. Under this mode of operation, the system was able to operate without external aeration and achieved a net P removal of 10.33 ±1.45 mg L −1 at an influent COD of 100 mg L −1 . No significant variation was observed in the reactor performance for different light intensities, indicating the EBPR-PAS system can be operated at low light intensities with a positive influence on P removal. Graphical Abstract: Image, graphical abstract